Nondestructive microimaging during preclinical pin-on-plate testing of novel materials for arthroplasty. (February 2014) - Teeter, Matthew G; Langohr, G Daniel G; Medley, John B; Holdsworth, David W
The purpose of this study was to determine the ability of micro-computed tomography to quantify wear in preclinical pin-on-plate testing of materials for use in joint arthroplasty. Wear testing of CoCr pins articulating against six polyetheretherketone plates was performed using a pin-on-plate apparatus over 2 million cycles. Change in volume due to wear was quantified with gravimetric analysis and with micro-computed tomography, and the volumes were compared. Separately, the volume of polyetheretherketone pin-on-plate specimens that had been soaking in fluid for 52 weeks was quantified with both gravimetric analysis and micro-computed tomography, and repeated after drying. The volume change with micro-computed tomography was compared to the mass change with gravimetric analysis. The mean wear volume measured was 8.02 ± 6.38 mm 3 with gravimetric analysis and 6.76 ± 5.38 mm 3 with micro-computed tomography (p = 0.06). Micro-computed tomography volume measurements did not show a statistically significant change with drying for either the plates (p = 0.60) or the pins (p = 0.09), yet drying had a significant effect on the gravimetric mass measurements for both the plates (p = 0.03) and the pins (p = 0.04). Micro-computed tomography provided accurate measurements of wear in polyetheretherketone pin-on-plate test specimens, and no statistically significant change was caused by fluid uptake. Micro-computed tomography quantifies wear depth and wear volume, mapped to the specific location of damage on the specimen, and is also capable of examining subsurface density as well as cracking. Its noncontact, nondestructive nature makes it ideal for preclinical testing of materials, in which further additional analysis techniques may be utilized.